A questionnaire to identify patellofemoral pain in the community: an exploration of measurement properties. Issue 1 (December 2016) - Dey, Paola; Callaghan, Michael; Cook, Neil; Sephton, Ruth; Sutton, Chris; Hough, Elaine; James, Jonathan; Saqib, Rukhtam; Selfe, James
Abstract Background Community-based studies of patellofemoral pain (PFP) need a questionnaire tool that discriminates between those with and those without the condition. To overcome these issues, we have designed a self-report questionnaire which aims to identify people with PFP in the community. Methods Study designs: comparative study and cross-sectional study. Study population: comparative study: PFP patients, soft-tissue injury patients and adults without knee problems. Cross-sectional study: adults attending a science festival. Intervention: comparative study participants completed the questionnaire at baseline and two weeks later. Cross-sectional study participants completed the questionnaire once. The optimal scoring system and threshold was explored using receiver operating characteristic curves, test-retest reliability using Cohen's kappa and measurement error using Bland-Altman plots and standard error of measurement. Known-group validity was explored by comparing PFP prevalence between genders and age groups. Results Eighty-four participants were recruited to the comparative study. The receiver operating characteristic curves suggested limiting the questionnaire to the clinical features and knee pain map sections (AUC 0.97 95 % CI 0.94 to 1.00). This combination had high sensitivity and specificity (over 90 %). Measurement error was less than the mean difference between the groups. Test–retest reliability estimates suggest good agreement (N = 51, k = 0.74, 95 % CI 0.52–0.91). The cross-sectional study (N = 110) showed expected differences between genders and age groups but these were not statistically significant. Conclusion A shortened version of the questionnaire, based on clinical features and a knee pain map, has good measurement properties. Further work is needed to validate the questionnaire in community samples.